2006
DOI: 10.1002/ajh.20467
|View full text |Cite
|
Sign up to set email alerts
|

Allografting in patients with severe, refractory aplastic anemia using peripheral blood stem cells and a fludarabine-based conditioning regimen: The Mexican experience

Abstract: We studied the effectiveness of a fludarabine/cyclophosphamide-based conditioning regimen without anti-thymocyte globulin in 23 aplastic anemia patients who had no response to previous conventional pharmacologic treatment. Patients received oral busulphan 4 mg/ kg/day/2 days, IV cyclophosphamide 350 mg/m 2 /day/3 days, and fludarabine 30 mg/m 2 /day/ 3 days. For GVHD prophylaxis, patients received MTX 5 mg/m 2 days +1, +3, +6, and +11 and oral cyclosporin A (CyA) 5 mg/kg/day, starting on day -1. Peripheral blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
21
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 26 publications
2
21
0
Order By: Relevance
“…In our study, despite the use of peripheral blood as the source of stem cells in patients with SAA, only 15.4% of 26 patients developed acute grades II–IV GVHD and 19% cGVHD, which was limited in all cases. These results are similar to those reported in a previous multicenter study in Mexico (39). Interestingly, in India, the use of a fludarabine‐based protocol and PBSCs in patients with SAA resulted in respective rates of aGVHD and cGVHD of 21% and 31%, with an OS of 85% (40).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, despite the use of peripheral blood as the source of stem cells in patients with SAA, only 15.4% of 26 patients developed acute grades II–IV GVHD and 19% cGVHD, which was limited in all cases. These results are similar to those reported in a previous multicenter study in Mexico (39). Interestingly, in India, the use of a fludarabine‐based protocol and PBSCs in patients with SAA resulted in respective rates of aGVHD and cGVHD of 21% and 31%, with an OS of 85% (40).…”
Section: Discussionsupporting
confidence: 92%
“…Previous reports on the use of PBSCs in the treatment of SAA have shown an increased incidence of cGVHD, in some cases with a high mortality (38). In contrast, it has been suggested that the use of non‐myeloablative conditioning regimens using fludarabine without high doses of cyclophosphamide is not associated with an increase in GVHD (39, 40), with acute and cGVHD presenting in 5–30% and 25–60% of patients, respectively. In our study, despite the use of peripheral blood as the source of stem cells in patients with SAA, only 15.4% of 26 patients developed acute grades II–IV GVHD and 19% cGVHD, which was limited in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The major cause of early mortality was sepsis, and this mortality is related to the fact that approximately 28% of patients had sustained fever or fungal infection at the time of HSCT. Our previous experience has shown us that waiting for resolution of infection meant that a majority may not ultimately make it to transplant, and it is possible to successfully transplant patients with aplastic anemia who have active fungal infection at the time of HSCT . The use of this conditioning regimen is associated with a good five‐yr overall survival of 75.8%.…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the risk of graft failure and improve outcome, modification of conditioning regimens using a fludarabine‐based conditioning has been attempted in a number of small studies . We have reported previously along with other groups the utility of using fludarabine‐based regimens in both heavily transfused patients as well as in patients with active infection at the time of HSCT . Fludarabine‐based regimens have also been used in patients undergoing unrelated stem cell transplants for SAA and as conditioning in older patients with SAA .…”
mentioning
confidence: 99%
“…In developing countries, patients generally have to pay for their transplants without any financial help from either the government or the insurance sector, and transplant physicians must choose the best time to take up a patient for HSCT, to avoid wasting too much of their scarce Cell dose (·10 8 MNC/kg) 5.8 (1.9-8.5) ANC >500/mm 3 11 d (9-14) ANC >1000/mm 3 12 d (10-15) Platelet count >20 000/mm 3 resources. Fludarabine-based protocols provide an attractive option for HSCT in patients with AA, as the minimal toxicity and rapid engraftment associated with these protocols make them ideal for use in patients with active infections (8,9,12). They are also associated with a considerable reduction in costs, making them suitable for use in developing countries (13,14).…”
Section: Discussionmentioning
confidence: 99%